Augmented reality treasure hunt game - Tan, Kean Hon (2024)
The title of this project is called “Augmented Reality Treasure Hunt Game”. The growing trend of mobile AR Treasure Hunt games encourages players to explore their environment and interact with augmented reality elements, all facilitated by the use of Mapbox API for location-based experiences. These games offer both entertainment and educational opportunities, though the current market lacks high-quality AR outdoor treasure hunts that integrate Mapbox effectively. Additionally, fostering interpersonal skills is paramount, necessitating multiplayer functionality to promote cooperation and communication. Regular updates are crucial for player engagement. This project adopts an Agile methodology with an iterative plan to address these challenges, encompassing five key modules: the Interface Module, AR Module, Game Logic Module, Location Services and Tracking Module, and the Database Module. Educational missions promote learning, while a cooperation module enhances player interaction and collaboration. Developed in Unity using C# and Mapbox API, the game allows players to work together, utilizing real-world maps to find virtual points and interact with AR elements while on a quest for treasure. Furthermore, the application permits users to create and join custom game flows, offering flexibility and extending the game's appeal. In short, this project target to forge a new platform that offers an exciting and engaging learning experience for players.